PENGARUH KECERDASAN EMOSIONAL, LINGKUNGAN KERJA DAN KOMITMEN PEGAWAI TERHADAP PRODUKTIVITAS KERJA PADA BADAN PERENCANAAN PEMBANGUNAN, PENELITIAN DAN PENGEMBANGAN DAERAH KABUPATEN TOJO UNA-UNA - Kanali, Ishak W. (Katalogis, 2017)
The study determines and analyzes simultaneous and partial influence of emotional quotient, work environment, and commitment on productivity in The Agency of Development Planning, Research, and Regional Development of Tojo Una-Una District. It applies quantitative approach by taking 38 officials in The Agency of Development Planning, Research, and Regional Development of Tojo Una-Una District as samples through census method. Technique of analysis is multiple linear regressions with hypotthetical test by using confidence level of α = 0,05 with SPSS version 22.00. validity test runs with corrected-item total correlation with minimum value of r=0.3. Reliability test applies cronbach alpha coefficient with coefficient limit of α >0.6. the results shows that emotional quotient, work environment, and commitment simultaneously have significnat influence on officials’ productivity in The Agency of Development Planning, Research, and Regional Development of Tojo Una-Una District with Fvalue of 2.045>Ftable of 0.049 on sig 0.000. The variable of emotional quotient has significant influence on productivity with tvalue of 1.523>ttable of 0.137 on sig 0.000; work environment has positive influence but insignificant on productivity with tvalue of 1.445>ttable of 0.158 on sig 0.162; commitment has significant influence on productivity tvalue of 4.518>ttable of 0.677 on sig 0.000.